HUBUNGAN DAYA TAHAN, KECEPATAN, DAN KELINCAHAN TERHADAP KEMAMPUAN BERMAIN FUTSAL SISWA SMP NEGERI 17 KELAS IX KOTA JAMBI - Jery Devon Pratama; Reza Hadinata; Ahmad Muzaffar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between endurance, speed, and agility and the futsal performance of ninth-grade students at SMP Negeri 17 in Jambi City. The research method used was a quantitative approach with a correlational design. The population for this study consisted of all ninth-grade students at SMP Negeri 17 in Jambi City, while the sample comprised 35 students selected using purposive sampling. Data were collected through the Multistage Fitness Test (Bleep Test) to measure endurance, the 30-Meter Sprint Test to measure speed, the Illinois Agility Test to measure agility, and a futsal performance test. Data analysis was performed using descriptive statistics, the Shapiro-Wilk normality test, Pearson’s product-moment correlation, and multiple linear regression with the assistance of SPSS software. The results showed a significant relationship between endurance and futsal playing ability, with a correlation coefficient of r = 0.990 and a p-value of 0.000 < 0.05. There was also a significant relationship between speed and futsal playing ability, with a correlation coefficient of r = -0.984 and a p-value of 0.000 < 0.05. There is a significant relationship between speed and futsal performance, with a correlation coefficient of r = -0.984 and a p-value of 0.000 < 0.05. There is a significant relationship between agility and futsal performance, with a correlation coefficient of r = -0.988 and a p-value of 0.000 < 0.05. The results of the multiple linear regression analysis showed an R value of 0.991 and an R-squared value of 0.982, with a significance level of 0.000 < 0.05. Thus, it can be concluded that endurance, speed, and agility collectively have a significant relationship with the futsal performance of ninth-grade students at SMP Negeri 17 in Jambi City.